Influence of role and competition stage on movement, heart rate and perceived task load characteristics of match officials during Men`s and Women`s Rugby League World Cup - Johnson, E.; Highton, J.; Twist, C. (Journal of Sports Sciences, 2025)
We examined the influence of rugby league match officials` role and competition stage on movement, heart rate and subjective task loads during international competition. Measures were recorded from all 28 match officials (male n = 25; female n = 3; 4 ± 3 matches per official) comprising 42 referees and 84 touch judge performances from Men`s (n = 29) and Women`s (n = 13) World Cup matches. More accelerations (p = 0.003) and decelerations (p = 0.013), higher mean heart rates (p = 0.006) and perceived physical load (p < 0.001) and less high-speed running (p = 0.002) occured in referees compared to touch judges. Distance, high-speed running, accelerations/decelerations, heart rate, and subjective mental, physical, temporal, effort and frustration loads (all p < 0.05) were higher during the Men`s compared to Women`s competition. Mean speed and high-speed running (all p < 0.05) decreased between halves in the Knockout stage, while subjective mental, physical, temporal and effort load increased (all p < 0.05). Declines in relative high-speed running between the halves were also greater during the Knockout stage (p = 0.016). The on-field role, the competition and stage influence the physical, heart rate and perceived task loads of rugby league match officials.